PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, PERTUMBUHAN PENJUALAN, DAN KEBIJAKAN DIVIDEN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE TAHUN 2014-2016 - Efrista Erlian Sari, 14.05.51.0165; Sudarsi, Sri (Students Journal of Economic and Management, 2018)
This study aims to examine and analyze the effect of firm size, profitability, sales growth, and dividend policy on capital structure. This study was conducted using secondary data. The population in this study are all companies incorporated in manufacturing companies listed on the Indonesia Stock Exchange 2014-2015. The sample in this study using purposive sampling method. The method of analysis used in this study is the method of multiple regression analysis. The result of this study proves that from the four variables used are firm size have positive and significant effect to capital structure, profitability have negative and significant effect to capital structure, sales growth has no significant effect to capital structure, and dividend policy has no significant effect to capital structure.Keywords: Company size, Profitability, Sales growth, Dividend policy, and Capital structure.